Proceedings of the Fifth ACM Conference on Recommender Systems 2011
DOI: 10.1145/2043932.2043996
|View full text |Cite
|
Sign up to set email alerts
|

Precision-oriented evaluation of recommender systems

Abstract: There is considerable methodological divergence in the way precision-oriented metrics are being applied in the Recommender Systems field, and as a consequence, the results reported in different studies are difficult to put in context and compare. We aim to identify the involved methodological design alternatives, and their effect on the resulting measurements, with a view to assessing their suitability, advantages, and potential shortcomings. We compare five experimental methodologies, broadly covering the var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
122
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 156 publications
(126 citation statements)
references
References 10 publications
2
122
0
2
Order By: Relevance
“…For instance, MAE is used in (Sarwar et al 2001) whereas hit-rate is used in (Deshpande and Karypis 2004). In prior work (Bellogín et al 2011a), we already observed an item-based method with low (i.e. good) RMSE and a close to zero precision, evidencing that a well performing method in terms of error metrics does not necessarily have a good performance in terms of precision.…”
Section: Item Ranking Taskmentioning
confidence: 92%
“…For instance, MAE is used in (Sarwar et al 2001) whereas hit-rate is used in (Deshpande and Karypis 2004). In prior work (Bellogín et al 2011a), we already observed an item-based method with low (i.e. good) RMSE and a close to zero precision, evidencing that a well performing method in terms of error metrics does not necessarily have a good performance in terms of precision.…”
Section: Item Ranking Taskmentioning
confidence: 92%
“…Besides, it is not possible to apply metrics such as MAE and RMSE to our approaches, since the proposed methods rank items, but do not generate rating predictions. The methodology used in the evaluation corresponds to the TestItems approach described in (Bellogín, Castells, and Cantador, 2011a), where, for each user, a ranking is generated by predicting a score for every item in the test set, only ignoring those items already rated by the user (i.e., in training). We also tested alternative methodologies, such as the one proposed by (Koren, 2008) where a ranking is generated for each item in the test set based on N additional not-relevant items.…”
Section: Evaluation Methodologymentioning
confidence: 99%
“…Based on the obtained predicted ratings, in case of RSVD, and obtained scores, in proposed model, top 5 and top 10 items are presented to the user. The predicted rating and predicted scores respectively in descending order are presented to every user and then accuracy measures such as precision are obtained [24]. figure 2 show the precision of the proposed cosine based latent factor model and RSVD on ml-100k dataset and FilmTrust dataset respectively.…”
Section: Evaluating the Performance Of Modelsmentioning
confidence: 99%